DDEL-05. Intraventricular therapy with topotecan is feasible and safe: Experience in 50 pediatric patients with various malignant brain tumors. (3rd June 2022) - Peyrl, Andreas; Stepien, Natalia; Mayr, Lisa; Azizi, Amedeo; Gojo, Johannes; Baumgartner, Alicia; Hedrich, Cora; Lippolis, Maria Aliotti; Slavc, Irene
Abstract: BACKGROUND: Malignant brain tumors carry a high risk for leptomeningeal dissemination, but the CSF compartment is often not affected by systemic therapy. Intraventricular therapy via an Ommaya reservoir is one possibility to increase the cytotoxic drug concentration in the CSF. Unfortunately, the number of drugs that can be administered directly into the CSF is limited. We report on our experience with topotecan administered via an Ommaya reservoir. PATIENTS AND METHODS: Between 2015 and 2021, 50 patients aged 1 to 22 years (mean and median both 8 years) with various malignant brain tumors received intraventricular topotecan via an Ommaya reservoir. Topotecan was administered at 0.4mg twice a week (>1 and <2 years 0.25mg, >2 and <3 years 0.32mg). RESULTS: In total, 1168 doses of topotecan (1-87/patient, mean 23, median 18) were administered at our department. Treatment was given over a period of 0-65 months (mean and median 33 months). Intraventricular treatment with topotecan was generally well tolerated. Two patients reported side effects. One boy with multiple recurrences of an ependymoma in the posterior fossa showed increased tremor after intraventricular administration of topotecan, another girl with recurrent medulloblastoma reported fatigue. CONCLUSION: Intraventricular therapy with topotecan is feasible and generally well tolerated. Topotecan can be an important addition for patients with recurrent malignant brain tumors to increase cytotoxic drug concentrations in CSF.